In Vivo Confocal Microscopy in Blepharitis Patients with Ocular Demodex Infestation. (18th August 2022) - Yildiz-Tas, Ayse; Arici, Ceyhun; Mergen, Burak; Sahin, Afsun
ABSTRACT: Purpose: To compare corneal in-vivo confocal microscopy (IVCM) findings in patients with seborrheic blepharitis with healthy controls and to evaluate the correlation with the Demodex load. Methods: Sixty-two Demodex positive seborrheic blepharitis patients and 24 controls were included. Four eyelashes from each eye were examined. The median value of Demodex count (5 mites/eye) was assigned as the cutoff value to create low and high Demodex infestation subgroups. Corneal nerve parameters (fiber length;CNFL, fiber density;CNFD, branch length;CNBL, branch density;CNBD) and dendritic cell density (DCD) were analyzed by IVCM for all participants. Results: The mean DCD of eyes in low (37.62 ± 25.18 cells/mm 2 ) and high (76.00 ± 44.00 cells/mm 2 ) Demodex load groups were significantly higher than those in the control group (14.25 ± 2.68 cells/mm 2 ) ( p < .001). CNFL, CNFD, CNBL and CNBD were significantly lower in low and high Demodex groups compared to controls ( p < .001). Conclusions: Demodex positive seborrheic blepharitis patients showed significantly reduced density of corneal nerves and elevated DCD levels.